2020
DOI: 10.3389/fendo.2020.00644
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability and Diabetic Neuropathy in Young Adults With Type 1 Diabetes

Abstract: Background: Glycemic variability (GV) may attribute to the pathogenesis of diabetic neuropathy. The aim of this cross-sectional study was to investigate the association between GV and distal symmetric polyneuropathy (DSPN) and cardiovascular autonomic neuropathy (CAN) in a Danish population of young adults with type 1 diabetes. Methods: Young adults between 18 and 24 years with type 1 diabetes were included in this cross-sectional study. CAN was assessed by cardiovascular autonomic reflex tests (CARTs) and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As described previously, the continuous glucose monitoring (CGM) sensor Enlite™ (Medtronic, Northridge, CA, USA) was inserted into the subcutaneous tissue of the abdomen or the upper arm and was worn for 5 days ( 24 ). The capillary finger blood glucose was monitored four times daily for calibration.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously, the continuous glucose monitoring (CGM) sensor Enlite™ (Medtronic, Northridge, CA, USA) was inserted into the subcutaneous tissue of the abdomen or the upper arm and was worn for 5 days ( 24 ). The capillary finger blood glucose was monitored four times daily for calibration.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies revealed that HbA1c variability calculated by SD was independently associated with the severity of peripheral neuropathy and cardiovascular autonomic neuropathy in patients with T2DM [ 75 , 76 ]. Conversely, a cross-sectional study including 133 young adults with type 1 diabetes mellitus (T1DM) suggested that GV might not be a risk factor for diabetic neuropathy [ 77 ]. Longitudinal studies are required to confirm the elaborated role of GV in the progression of DPN.…”
Section: The Role Of Gv In Diabetic Macrovascular and Microvascular Cmentioning
confidence: 99%
“…Similarly, Nyiraty et al revealed that GV marker calculated by SD and mean absolute glucose were associated with the severity of CAN in patients with T1DM 50 . Nevertheless, in a cross-sectional observational study including 133 young adults with T1DM from 18 to 24 years, Christensen et al reported that after adjusting for risk factors and multiple tests, only higher MAGE was associated with slightly increasing measures of heart rate variability, indicating that GV might not be a risk factor for CAN in young adults with T1DM 51 .…”
Section: Gv and Canmentioning
confidence: 99%